Chemical Structural Elucidation and Immunomodulatory Activity of a New Polysaccharide from Saposhnikoviae Radix - Cui, Yifang; Fan, Haitao; Sun, Meng; He, Xinyang; Li, Jie; Tu, Guangzhong; Jiang, Yanyan; Liu, Bin (Planta Medica, 2025)
The chemical structure and immunomodulatory activity of a new homogeneous polysaccharide, SP4002501, isolated from Saposhnikoviae Radix (SR), were investigated. Purification of SP4002501 was performed by DEAE-Cellulose and Sepharose CL-6B column chromatography. The monosaccharidic constituents were identified as rhamnose (Rha), galacturonic acid (GalA), galactose (Gal), and arabinose (Ara) with a molar ratio of 3.7: 86.6: 2.7: 7.1. According to the methylation analysis, partial hydrolysis, FT-IR, and NMR analysis, SP4002501 had a backbone of polygalacturonic acid units with a small amount of galactose (Gal). Side chains are connected to C-3 of galactose (Gal) and consist of rhamnose (Rha), galacturonic acid (GalA), galactose (Gal), and arabinose (Ara), with arabinose (Ara) as terminal sugar. Biological activity assessment suggests that SP4002501 exhibits immunomodulatory activity through promoting macrophage proliferation and phagocytosis.
Keywords: polysaccharide; Saposhnikoviae Radix; Saposhnikovia divaricata; Apiaceae; chemical structure; immunomodulatory activity